Genre Practices, Multimodality and Student Identities - Gray, Robert James (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers a novel framework for describing and understanding student identity via the central concept of "genre practices", developed through an empirical focus on multimodality within the genre of English as a medium of instruction (EMI) undergraduate presentations. The author draws on interviews with undergraduate psychology students and recordings of their presentations to argue that by engaging in the multimodal practices of classroom presentations, presenters (re)produce both the genre and their identities as students. The resulting theory of student identity is widely applicable to tertiary settings, and the methodology described is applicable to the study of practices and identity in a range of other classroom genres. The book will therefore be of interest not only to researchers in EMI and TESOL settings, but also any tertiary-level educational practitioners whose courses include presentations.
Chapter 1: Introduction -- Chapter 2: The Research Setting -- Chapter 3: The Classroom Presentation Genre -- Chapter 4: A Framework for Analysing Student Identity -- Chapter 5: Student Identity: Presentations and Intersections -- Chapter 6: Core Student Identity in Classroom Presentations -- Chapter 7: Identity Alignments in Classroom Presentations -- Chapter 8: Discussion and Conclusion.
Keywords: Language acquisition; Language and languages-Study and teaching; Educational psychology; Language Acquisition and Development; Language Education; Educational Psychology; Language Teaching and Learning